(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Interview with Josette Féral held in September 2019 in the city of Lisbon, host of the annual EASTAP conference. In it, the interviewee discusses the various meanings of the performative, indicates what seduces her on the scene and what is significant in the field of contemporary theatrical theory.